JAZ Repressors: Potential Involvement in Nutrients Deficiency Response in Rice and Chickpea - Singh, Ajit P.; Pandey, Bipin K.; Deveshwar, Priyanka; Narnoliya, Laxmi; Parida, Swarup K.; Giri, Jitender (Frontiers in Plant Science, 2015)
Jasmonates (JA) are well-known phytohormones which play important roles in plant development and defense against pathogens. Jasmonate ZIM domain (JAZ) proteins are plant-specific proteins and act as transcriptional repressors of JA-responsive genes. JA regulates both biotic and abiotic stress responses in plants; however, its role in nutrient deficiency responses is very elusive. Although, JA is well-known for root growth inhibition, little is known about behavior of JAZ genes in response to nutrient deficiencies, under which root architectural alteration is an important adaptation. Using protein sequence homology and a conserved-domains approach, here we identify 10 novel JAZ genes from the recently sequenced Chickpea genome, which is one of the most nutrient efficient crops. Both rice and chickpea JAZ genes express in tissue- and stimuli-specific manners. Many of which are preferentially expressed in root. Our analysis further showed differential expression of JAZ genes under macro (NPK) and micronutrients (Zn, Fe) deficiency in rice and chickpea roots. While both rice and chickpea JAZ genes showed a certain level of specificity toward type of nutrient deficiency, generally majority of them showed induction under K deficiency. Generally, JAZ genes showed an induction at early stages of stress and expression declined at later stages of macro-nutrient deficiency. Our results suggest that JAZ genes might play a role in early nutrient deficiency response both in monocot and dicot roots, and information generated here can be further used for understanding the possible roles of JA in root architectural alterations for nutrient deficiency adaptations.